Pemberdayaan Masyarakat Melalui Penerapan Belajar Kognitif Dengan Konsep Komunikasi Instruksional Di Pondok Pesantren Yatim Piatu Hayyussalam Kramat Watu Kabupaten Serang - Indrianti Azhar Firdausi; Nanang Karnato (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2019)
The efforts of Hayyussalam Orphanage Islamic Boarding School to improve knowledge and change attitudes are constrained by the lack of education and care workers. The purpose of this activity is to overcome these problems, namely to do teaching and mentoring with the concept of instructional communication and cognitive learning theory, where learning partners can change the way of thinking, form meaning and execute instructions well from instructional materials. From the activities that have been carried out with the results of the results through the teaching method and mentoring percentage of 100%, the addition of insight and attitude changes 90%. Orphanage children as active and enthusiastic partners in participating in activities.